1999
DOI: 10.1021/ac990417r
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity Assay for Pesticide Using a Peroxidase as Chemiluminescent Label

Abstract: The application of a newly isolated transgenic tobacco peroxidase (TOP) as a chemiluminescent label for immunoassay purposes is described for the first time. The enzyme has been oxidized with m-periodate and subsequently coupled to the model compound 2,4-dichlorophenoxyacetic acid (2,4-D) using a carbodiimide method. As compared to the native horseradish peroxidase used in control experiments, the TOP enzyme showed significantly higher efficiency of coupling to the antigen and no loss of the specific activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 16 publications
0
26
0
4
Order By: Relevance
“…In addition to the stability of the enzyme in an alkaline medium, the above property is responsible for the fact that the activity of TOP in a luminescence reaction is higher than that in an enhanced chemiluminescence reaction catalyzed by HRP by an order of magnitude [7]. This property of TOP was clearly demonstrated in studies performed in cooperation with our colleagues from the University of Lund using chemiluminescence enzyme immunoassay for a number of pesticides as an example [8]. The sensitivity of TOP in a luminescence reaction is highly competitive with that of recently isolated palm peroxidase [22].…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…In addition to the stability of the enzyme in an alkaline medium, the above property is responsible for the fact that the activity of TOP in a luminescence reaction is higher than that in an enhanced chemiluminescence reaction catalyzed by HRP by an order of magnitude [7]. This property of TOP was clearly demonstrated in studies performed in cooperation with our colleagues from the University of Lund using chemiluminescence enzyme immunoassay for a number of pesticides as an example [8]. The sensitivity of TOP in a luminescence reaction is highly competitive with that of recently isolated palm peroxidase [22].…”
mentioning
confidence: 87%
“…In addition to the fundamental studies of natural glycosylated TOP performed in 1996-1999 [3][4][5][6], which demonstrated a number of practically promising properties of this enzyme, the new enzyme was also tested for analytical purposes [7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
mentioning
confidence: 99%
“…The sensitivity of an immunoassay is very dependent on the affinity of the specific antibodies and on the sensitivity of the detection method, however. The enhanced chemiluminescence (ECL) reaction offers the possibility of improving the sensitivity of immunoassays by at least two orders of magnitude compared with conventional colorimetric detection [28,29]. HRP is commonly used in CL detection based on the luminol-H 2 O 2 -HRP-PIP (p-iodophenol) enhanced chemiluminescent system [30].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of chemiluminescent (CL) reagents to reveal the formation of immunocomplexes in enzyme-linked immunosorbent assays (ELISAs) already led to an improvement in the sensitivity, a wider range of detected concentrations, and lower consumption of immunoreagents compared with colorimetric (COL) endpoint detection (Dzgoev et al 1999). Because they are ready to use from commercial sources, CL reagents are not toxic, and their advantages related to the development of specific, sensitive, and reliable immunoassays are further enhanced by the low cost, simplicity, and availability of portable and automatable instrumentation required for luminescent detection (Mickova et al 2005).…”
Section: Introductionmentioning
confidence: 99%